2018
DOI: 10.31254/jmr.2018.4401
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Associated Posterior Reversible Encephalopathy Syndrome (PRES): About a case

Abstract: The Posterior reversible encephalopathy syndrome (PRES) is a clinico-radiological syndrome, it may occur due to a number of causes, including the use of immunosuppressive treatments. It is a rare entity. We report here the occurrence of a PRES syndrome in a patient treated with tacrolimus after liver transplantation, revealed by ocular manifestations associated with intermittent headaches of moderate intensity and tremor in the hands later complicated by a condition epilepticus. The brain scan showed an occipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A 2016 review of PRES after liver transplantation also found that most cases developed 2 to 3 months after transplantation ( 12 ). In independent case reports, the longest time elapsed from transplantation to development of PRES was 110 days ( 3 ), though most were within the first month ( 1 , 2 ). To our knowledge, this case represents the longest documented time elapsed between liver transplantation and the development of PRES (3 years) in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…A 2016 review of PRES after liver transplantation also found that most cases developed 2 to 3 months after transplantation ( 12 ). In independent case reports, the longest time elapsed from transplantation to development of PRES was 110 days ( 3 ), though most were within the first month ( 1 , 2 ). To our knowledge, this case represents the longest documented time elapsed between liver transplantation and the development of PRES (3 years) in the existing literature.…”
Section: Discussionmentioning
confidence: 99%